(untitled) (UMRAN - Journal of Islamic and Civilizational Studies, 2016)
Ketika Cinta Bertasbih that has been written by Habiburrahman El-Shirazy is considered as a leading Islamic pop novel in Indonesia and also received an overwhelming response from fans in Malaysia. This is due to the practice of morality and responsibility values that applied by the author. This novel emphasizes the fundamental tenets of the Islamic fundamentals which contributes to the creation of a holistic overview of Islam. Hence, this paper aims to study and analyze the use of fundamental law committed by the author of the novel Ketika Cinta Bertasbih. This research used a content analysis method by applying document analysis as the main methods of data collection. The results of this study showed that Habiburrahman as the author of this novel have used the fundamental laws through the use of fictional framework that meets the legal framework outlined by the tenets of Islam.